English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4(cos^6x+sin^6x) = 1+3cos^2 2x

2006-12-16 12:26:55 · 1 answers · asked by Becker 1 in Science & Mathematics Mathematics

prove that 4(cos^6 x + sin^6 x) is equal to 1+3cos^2 2x

2006-12-16 14:09:24 · update #1

1 answers

4(cos^6x+sin^6x) = 4 (cos^2x + sin^2x)(sin^4x + cos^4x - sin^2x*cos^2x)
= 4 ( 1 - 3sin^2x*cos^2x) = 4 - 6 sin2x
=>1 + 3cos^2 2x = 4 - 6sin2x
<=>4 - 3sin^2 2x = 4 - 6 sin2x
<=> sin^2 2x - 2sin2x = 0
<=> sin2x( sin2x - 2) =0
<=> sin2x =0 <=> x = k*pi/2 ( k * 90 ) with k is an integer

2006-12-16 13:06:39 · answer #1 · answered by James Chan 4 · 0 0

fedest.com, questions and answers